1968
DOI: 10.1136/gut.9.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ABO blood groups and secretor status on bleeding and on perforation of duodenal ulcer.

Abstract: ABO BLOOD GROUPS IN RELATION TO DUODENAL ULCERSince Aird, Bentall, Mehigan, and Roberts (1954) convincingly demonstrated a high incidence of blood group 0 in duodenal ulcer subjects there have been a number of confirmatory studies carried out in different ethnic groups and populations (McConnell, 1966). Studies have also been undertaken to see if there is an especially strong association between blood group 0 and some particular category of duodenal ulcer patient. Brown, Melrose, and Wallace (1956) found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Little is known about the consequences of these differences. However, a higher risk of gastrointestinal bleeding complications is described for patients with group O blood, 6–9 whereas a higher incidence of ischemic heart disease and thromboses is reported in persons with the other ABO blood groups 10–15 …”
mentioning
confidence: 99%
“…Little is known about the consequences of these differences. However, a higher risk of gastrointestinal bleeding complications is described for patients with group O blood, 6–9 whereas a higher incidence of ischemic heart disease and thromboses is reported in persons with the other ABO blood groups 10–15 …”
mentioning
confidence: 99%
“…A large body of evidence suggests that this maintenance may be because of numerous tradeoffs surrounding host-microbe interactions. For example, nonsecretors are resistant to infection with the Norwalk (Noro) (17) and respiratory viruses (18) but are more susceptible to duodenal ulcers (19), rheumatic fever (20), and cholera (21). Furthermore, the breast milk of secreting mothers provides protection against Campylobacter jejuni to their offspring by exploiting the binding affinity of the bacterium to fucosyloligosaccharides (22).…”
mentioning
confidence: 99%
“…A lower plasma concentration of coagulation factor VIII is found in patients with group 0 compared to group A (43), but the clinical significance of this is uncertain. Apparently the bleeding tendency of patients with group 0 is only found in the gastric and duodenal mucosa, not in the uterine muscosa as demonstrated in metrorrhagia (19). Horwich et al found, in a group of patients with gastrointestinal haemorrhage and no demonstrable ulcer during X-ray examination, a significant excess of group 0, and considered diagnostic error a possible explanation of this (26).…”
Section: Resultsmentioning
confidence: 96%